IS26 Family Members IS257 and IS1216 Also Form Cointegrates by Copy-In and Targeted Conservative Routes - Christopher J. Harmer (American Society for Microbiology, 2020)
ABSTRACT IS26 has been shown to form cointegrates both by a copy-in mechanism involving one insertion sequence (IS) and a target and by a targeted conservative mechanism involving two ISs. IS26 is the flagship of a group of 65 bacterial ISs in the recently redefined IS6/IS26 family. Here, whether other family members can also use two mechanisms was examined using members of the IS257/IS431 and IS1216 isoform groups, which are associated with antibiotic resistance genes in staphylococci and enterococci, respectively. Transposases Tnp257 and Tnp1216 have 39% and 47% amino acid identities, respectively, with Tnp26 and are 62% identical to one another. Using a novel transposition assay, pUC-based plasmids carrying these ISs integrated into the chromosome of a temperature-sensitive polA Escherichia coli strain grown at the restrictive temperature. In the cointegrates, the plasmid carrying IS257 was flanked by various 8-bp target site duplications, consistent with random target selection. However, in a mating-out assay, only the targeted conservative reaction was detectable at a low frequency in a recA-negative E. coli strain, indicating that IS257 is at least 100-fold less active than IS26. For IS1216, in mating-out assays, both copy-in and targeted conservative cointegrate formation were detectable at frequencies similar to those observed for IS26. Duplication of various 8-bp target sites was detected for the copy-in route. For both IS257 and IS1216, when both of the plasmids carried an IS, the targeted conservative route occurred at a significantly higher frequency than the copy-in route, and only cointegrates formed by the conservative route were detected. IMPORTANCE IS26 differs from other studied ISs in the reactions that it can undertake. The differences make IS26 uniquely suited to its key role in the recruitment and spread of antibiotic resistance genes in Gram-negative bacteria. However, whether other ISs in the IS6/IS26 family can perform the same reactions is not known. IS257/IS431 and IS1216 isoforms found associated with antibiotic resistance genes in the Gram-positive bacteria staphylococci, enterococci, streptococci, and clostridia are related to IS26. However, the way that they move had not been investigated, limiting interpretation of their role in resistance gene dissemination and in the formation of cointegrates and complex resistance regions in staphylococci and enterococci. Here, they are shown to share the broad catalytic capabilities of IS26, demonstrating that it is likely that all members of the redefined IS6/IS26 family of bacterial ISs likewise are able to use both the copy-in and conservative routes.